Mary Lee Bendolph, Gee's Bend quilts, and beyond - Cubbs, Joanne; Arnett, Matthew Flint; Friis-Hansen, Dana 1961- (Tinwood Books, 2006)
The exhibition focuses on the quilts of Mary Lee Bendolph, and includes quilts by her mother Aolar Mosely, daughter Essie Bendolph Pettway, and daughter-in-law Louisiana P. Bendolph, found-object sculpture and assemblage by Thornton Dial and Lonnie Holley, and intaglio prints by Mary Lee and Louisiana Bendolph